Multiple Long-Term Conditions and Disability are Independently Associated with Higher Risk of Fall Among Community Adults: a Cross-Sectional Study - Alenazi AM; Alhwoaimel NA; Alqahtani BA; Alshehri MM; Alhowimel AS; Khunti K; Alghamdi MS (Dove Medical Press, 2024)
Aqeel M Alenazi,1 Norah A Alhwoaimel,1 Bader A Alqahtani,1 Mohammed M Alshehri,2 Ahmed S Alhowimel,1 Kamlesh Khunti,3 Mohammed S Alghamdi4 1Department of Health and Rehabilitation Sciences, Prince Sattam Bin Abdulaziz University, Al-Kharj, Saudi Arabia; 2Department of Physical Therapy, Jazan University, Jazan, Saudi Arabia; 3Diabetes Research Centre, University of Leicester, Leicester General Hospital, Gwendolen Road, Leicester, UK; 4Department of Medical Rehabilitation Sciences, Umm Al-Qura University, Makkah, Saudi ArabiaCorrespondence: Aqeel M Alenazi, Department of Health and Rehabilitation Sciences, College of Applied Medical Sciences, Prince Sattam Bin Abdulaziz University, Alt-Kharj, 11942, Saudi Arabia, Tel +966115886354, Email aqeelalenazi.pt@gmail.com; aqeel.alanazi@psau.edu.saBackground: Previous studies have suggested an association between falls and the presence of Multiple Long-Term Conditions (MLTC) or disabilities. However, there is limited understanding of how these factors independently or collectively contribute to the risk of falls and fear of falling among community-dwelling adults.Objective: This study examined the independent association between MLTC and the presence of disability with the risk of falls among community adults.Methods: A cross-sectional study included 324 adults (age ≥ 50). Demographic and clinical data included age, sex, body mass index (BMI), MLTC (≥ two chronic diseases) risk of fall (ie, history of fall in the previous 12-months, number of falls, and recurrent falls). The Barthel Index and Falls Efficacy Scale-International (FES-I) were used to assess disability and fear of fall, respectively.Results: MLTC (Odds Ratio (OR) 2.50, 95% Confidence Interval (CI) [1.26, 4.95], p=0.009), and disability (OR 1.71, 95% CI [1.04, 2.79], p = 0.034) were independently associated with history of falls. MLTC (Incidence Rate Ratio (IRR) 2.87, 95% CI [1.93, 4.29], p < 0.001) and disability (IRR 1.86 95% CI [1.46, 2.36], p < 0.001) were independently associated with an increased number of falls. MLTC (OR 4.50, 95% CI [1.78, 11.36], p = 0.001) and disability (OR 2.82, 95% CI [1.58, 5.05], p < 0.001) were independently associated with recurrent falls. MLTC (B = 6.45, p < 0.001) and disability (B = 3.05, p = 0.025) were independently associated with increased fear of falling.Conclusion: This study indicated that both MLTC and disability are independently associated with falls, number of falls and fear of falling in this population.Keywords: falling, disabilities, impairments, functional limitations, multiple chronic diseases, multimorbidity, Saudi